(untitled) (INTERNATIONAL SEMINAR, 2024)
This study examines the impact of AI-powered reading applications on the literary analysis skills of English Literature students. With the increasing integration of artificial intelligence in educational technology, these reading apps offer a range of interactive features that may support students in interpreting and analyzing texts. Using a qualitative case study approach, this research involved 10- 15 students who regularly use AI-powered reading apps. Data was collected through semi-structured interviews, observations, and analysis of students’ work, focusing on their engagement with app features that support critical reading and analysis. The findings reveal the ways AIdriven features—such as interactive annotations, contextual summaries, and analytical prompts—help students improve their interpretive skills. Additionally, this study highlights challenges, including over-reliance on automated interpretations and occasional limitations in app-generated insights. The results contribute valuable insights for educators seeking to integrate AI-driven tools in literature education and suggest practical recommendations for enhancing students’ analytical proficiency through technology.